ANALYSIS OF ERROR IN SOLVING PROBLEMS PISA CONTENT CHANGE AND RELATIONSHIP ON STUDENTS OF CLASS VIII MTs DARUL IMAN PALU USING NOLTING THEORY - Rahmatia; Evie Awuy (Jurnal Prinsip Pendidikan Matematika, 2022)
This qualitative research describes the types of errors made by class VIII students of MTs Darul Iman Palu in solving PISA problems with Change and Relationship content using the Nolting theory. Data were collected by test and interview methods. The research subjects consisted of two students, each having high and medium abilities. The results showed that (1) the types of errors made by high-ability students in solving PISA questions of Change and Relationship content based on Nolting's theory were misread-direction errors (errors in reading instructions). (2) The types of errors made by moderately capable students in solving PISA questions of Change and Relationship content based on Nolting's theory are misread-direction errors (errors in reading instructions) and concept errors (concept errors).